The Importance of Religious Tourism for Development of Sustainable Tourism: The Case of the Baptism Site in Jordan - JAWABREH, Omar A. A.; FAHMAWEE, Emad Al Dein AL; ALSHATNAWI, Ehab; ALANANZEH, Omar (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022, 2022)
Aim: The study aims to investigate and find the importance of religious tourism for the development of sustainable tourism: the case of the baptism site in Jordan. Materials and Methods: We used the SPSS version 20 to analyze 19 items of the Likert scale for the outcome in factor analysis. Before conducting the axial variable analysis, the suitability of the data for factor analysis was evaluated. Results and discussions: traditional industries have been phased out and replaced by tourism activities at the Baptism Site, which have a high tourist potential, resulting in increased economic growth in these areas. Conclusions: On the eastern bank of the Jordan River separating Jordan and Palestine, at the Baptism site, a world archaeological and heritage site, sustainable tourism has become a tool on which many foreign tourism institutions are focused. The result shows that environmental impacts were positively associated with sustainability issues.